Analisis Efektivitas Program Penyuluhan Pertanian Dalam Meningkatkan Produktivitas Kelompok Tani Di Kecamatan Panceng, Kabupaten Gresik - A, Evany Khairunnisa; Djazuli , Raden Achmad (CV.ITTC INDONESIA, 2024)
This study aims to analyze the effectiveness of agricultural extension programs in increasing the productivity of farmer groups in Panceng District, Gresik Regency. The research method uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 50 farmers who were members of farmer groups selected by purposive sampling. Data were collected through questionnaires, observations, and documentation, then analyzed using paired t-test and multiple linear regression. The results showed a significant increase in knowledge (t=8.742, p<0.001), skills (t=7.253, p<0.001), and farmer productivity (t=6.891, p<0.001) after participating in the extension program. Factors that significantly influence productivity improvement include extension intensity (β=0.412, p<0.01), extension methods (β=0.328, p<0.05), and farmer participation level (β=0.276, p<0.05). This study concludes that the agricultural extension program is effective in increasing the productivity of farmer groups in Panceng District, with recommendations to increase the intensity and quality of extension and encourage active farmer participation.